2008
DOI: 10.1890/07-1278.1
|View full text |Cite
|
Sign up to set email alerts
|

Sulfur Isotopes Link Overwinter Habitat Use and Breeding Condition in Double-Crested Cormorants

Abstract: North American Double-crested Cormorant (Phalacrocorax auritus) populations have increased greatly. Both breeding and overwintering ground factors have likely contributed to these increases. However, demonstrating how overwintering conditions may affect breeding birds has not been possible because of the difficulty in linking breeding birds to their wintering grounds. Here, we demonstrate the utility of stable sulfur isotopes to elucidate overwintering habitat use by cormorants breeding on Lake Erie. Sulfur is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
46
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(48 citation statements)
references
References 35 publications
1
46
1
Order By: Relevance
“…Marine sulphate generally has higher δ 34 S values (21‰ for phytoplankton) than terrestrial or freshwater derived sulphates (2–8‰ for upland plants) and therefore sulphur isotope analysis has been extensively used in species that use estuarine habitats (Peterson & Howarth, 1987; Connolly et al , 2004; Olin et al , 2012). In addition to directly tracing nutrient sources to an organism, δ 34 S has been used to track migratory behaviours of birds, regarding overwintering and breeding habitats (Lott et al , 2003; Hebert et al , 2008), and to reconstruct Chinook salmon Oncorhynchus tshawytscha (Walbaum 1792) life history from the larval to adult stages (Weber et al , 2002).…”
Section: Alternative Stable‐isotope Tracersmentioning
confidence: 99%
“…Marine sulphate generally has higher δ 34 S values (21‰ for phytoplankton) than terrestrial or freshwater derived sulphates (2–8‰ for upland plants) and therefore sulphur isotope analysis has been extensively used in species that use estuarine habitats (Peterson & Howarth, 1987; Connolly et al , 2004; Olin et al , 2012). In addition to directly tracing nutrient sources to an organism, δ 34 S has been used to track migratory behaviours of birds, regarding overwintering and breeding habitats (Lott et al , 2003; Hebert et al , 2008), and to reconstruct Chinook salmon Oncorhynchus tshawytscha (Walbaum 1792) life history from the larval to adult stages (Weber et al , 2002).…”
Section: Alternative Stable‐isotope Tracersmentioning
confidence: 99%
“…Expansion of the aquaculture industry in the LMRV has likely enhanced the food supply for wintering cormorants (Weseloh and Ewins , Glahn et al , Blackwell et al , Hebert et al , King et al ). Studies of cormorants collected in the Mississippi Delta have shown that they improve their overwinter body condition by foraging at aquaculture facilities (Glahn and Stickley , Glahn et al ).…”
mentioning
confidence: 99%
“…Peak exposure to infection occurs early in the breeding season with dissipating exposure as the season progresses (Rausch 1983). Furthermore, there is some suspicion that male and female cormorants use different habitats (Tobin et al 2002, Hebert et al 2008): a suspicion that was confirmed for the birds used in this study with stable isotope analysis (Robinson et al unpubl. data).…”
Section: Discussionmentioning
confidence: 57%